Data centralisation as a key enabler of digital transformation in South African banks - Monyamane, Keitumetse Lucy (University of the Witwatersrand, Johannesburg, 2024)
This research report investigates the inhibitors of data centralisation in digital transformation. The study focuses on retail banks in South Africa, as these institutions aim to become customer-centric. However, the adoption of digital technologies and data strategy implementation are cumbersome due to legacy systems. The existing theoretical framework is that organisations undergoing a transformation need to understand how to adopt and implement new technology. It leverages emerging technologies, strategic organisational direction, and competitive factors as drivers for adoption. Literature specifies that there needs to be an informed digital culture and data operating model championed by leadership to ensure organisational change. Retail banks face challenges as they hold valuable customer data to offer exceptional user experience but have challenges becoming data-driven organisations due to silos, bureaucracy, and implantation capabilities. Qualitative research, in the form of semi-structured interviews, was conducted with executives and middle management from the top three retail banks in South Africa. The study found that there is a gap in data strategy formation to address a digital strategy, silos in the operating model, data roles and skills, data-driven culture and implementation challenges to manage data and integrate to new technologies. It was found that data centralisation requires the support of a leadership drive. Several challenges were highlighted in line with the research questions, and recommendations were proposed: lead a data-driven strategy, adopt a customer- centric culture, expand data capabilities, centralise data management, and modernise architecture and technology
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Digital transformation; Data strategy; Data centralisation; Customer centricityg; Digital culture; Retail bankin; UCTD; SDG-9: Industry, innovation and infrastructure